Evaluation of Modified Frailty Index-5 as a Predictor of 60-day Perioperative Morbidity and Mortality in Geriatric Patients Presenting for Orthopaedic Surgery: A Prospective Cohort Study - Aparna Ashay Nerurkar; Amreen Fatima (Journal of Clinical and Diagnostic Research)
Introduction: Frailty indices predicting perioperative adverse outcomes have been used predominantly in retrospective studies for prediction of surgical adverse outcomes. Aim: To evaluate the modified 5-item Frailty Index (mFI-5) as a predictor of anaesthetic and surgical complications up to 60 days in geriatric patients presenting for orthopaedic surgery. Materials and Methods: The prospective cohort study was conducted at Lokmanya Tilak Municipal General Hospital, Mumbai, Maharashtra, India, from December 2019 to December 2020. Details of participants and caregivers, mFI-5 scores and surgical details of 62 patients aged >65 years undergoing orthopaedic surgeries were studied. The mFI-5 score was calculated based on the presence of five co-morbidities: Congestive Heart Failure (CHF), Diabetes Mellitus (DM), Chronic Obstructive Pulmonary Disease (COPD) or pneumonia, functional health status and hypertension, as defined in NSQIP database. Complications of perioperative bleeding and inotropic support, along with others mentioned in the National Surgical Quality Improvement Program (NSQIP) database, were noted up to 60 days, with milestones of 48 hours, seven days and 30 days. The data were analysed for association between mFI-5 and complications by applying t-test, Chi-square test and multivariate analysis using the Statistical Package for the Social Sciences (SPSS) 20.0 version. Results: Mean age was 71.44±6.70 years, with 26 patients having an mFI-5 >3 (mean 2.33±0.96). Forty-five patients had at least one complication (mean 2.39±2.59). Mortality was observed in three out of 26 patients with an mFI-5 >3 (11.54%), while one in 36 patients (2.78%) died with mFI-5<3. No association with mortality was observed with either unit increase in mFI-5 scores or mFI-5>3. Complications included use of blood and blood products, inotropes and postoperative ventilation in the first 48 hours (mean 0.73±0.75), respiratory complications and blood and blood product transfusions in the 48 hours to seven days period (mean 0.65±1.13), Surgical Site Infections (SSIs) and reoperations between 8-30 days (mean 0.74±1.41) and renal insufficiency and death in the 30-60 days period (mean 0.27±0.61). Age (p-value=0.315), gender (p-value=0.635), scheduling (p-value=0.530), site (p-value=0.077) and nature of surgery (p-value=0.172) were not statistically significant, while mFI scores ≥3 (p-value <0.001), American Society of Anaesthesiologists (ASA) grades (p-value=0.016), surgical duration (p-value=0.012), CHF (p-value=0.003) and DM (p-value=0.002) were statistically significant. Conclusion: Patients aged >65 years with mFI-5 scores ≥3, having CHF, DM, ASA grades >2, undergoing orthopaedic surgeries of duration up to three hours, had statistically significant chance of developing postoperative complications, other than death, up to 60 days. A randomised controlled trial with mFI-5 cut-off of ≥3 and longer follow-up periods would yield better results.